A vocabulary of desire the Song of Songs in the early synagogue - Lieber, Laura Suzanne (Leiden Boston Brill, 2014)
"In A Vocabulary of Desire, Laura Lieber offers a nuanced, multifaceted and highly original study of how the Song of Songs was understood and deployed by Jewish liturgical poets in Late Antiquity (ca. 4th-7th centuries CE). Through her examination of poems which embellish and even rewrite the Song of Songs, Lieber brings the creative spirit-liturgical, intellectual, and exegetical-of these poems vividly to the fore. All who are interested in the early interpretation of the Song of Songs, the ancient synagogue, early Jewish and Christian hymnography, and Judaism in Late Antiquity will find this volume both enriching and accessible. The volume consists of two interrelated halves. In the first section, four introductory essays establish the broad cultural context in which these poems emerged; in the second, each chapter consists of an analytical essay structured around a single, complete poetic cycle, presented in new Hebrew editions with annotated original English translations"--
Part I: Essays. 1. "A garden enclosed": the Song of Songs as a gateway to synagogue poetry -- 2. "Let him kiss me": the place of piyyut in the history of interpretation of the Song -- 3. "Your voice is sweet": piyyut as an extension of biblical rhetoric -- 4. "I am my beloved's and his desire is for me": the world of the Songs -- Part II: Texts and commentary, translator's introduction. 5. A love song to the Torah: anonymous, qedushta Shir ha-Shirim -- 6. Lyrics of love: Yannai, shivata Shir ha-Shirim -- 7. Of ritual and reciprocity: Yannai, qedushta Shir ha-Shirim -- 8. The power of dew: Eleazar Birabbi Qallir, shivata for dew -- 9. Youthful love is eternal: Eleazar Birabbi Qallir, the groom's qedushta -- 10. Like stars of light: Eleazar (Birabbi Qallir?), yotzer Shir ha-Shirim.
"This volume examines six piyyutim ... 1. An anonymous qedushta shel sheva for Passover (ca. fifth century) ; 2. A shivata for Passover by Yannai (sixth century) ; 3. A qerova for Passover by Yannai ; 4. A shivata for the Prayer for Dew by Eleazar birabbi Qallir (late sixth-early seventh century) ; 5. A qedushta for the first Sabbath following a wedding by Eleazar birabbi Qallir ; 6. A yotzer for Passover by Eleazar birabbi Qallir"--ECIP introduction.
Includes bibliographical references (pages 411-419) and index.
Keywords: Piyutim -- Criticism, Textual; Biblia -- Criticism, interpretation, etc; 296*512 -- Synagogale schriftlezingen; 296*515 -- Geschiedenis van de joodse liturgie en verschillende riten: Asjkenazi; Sefardisch; Jemenitisch; 933.52 -- Geschiedenis van het Joodse volk: Byzantijnse tijd--(325-638); 223.6 -- Hooglied